Impact of Transportation Network Companies on Conventional Taxi Companies in Indonesia - Setiawan, Andy; Maulana, Agus (KnE Social Sciences, 2024)
This research was conducted to determine the impact of disruptive innovations with the emergence of online-based transportation on conventional taxi companies in Indonesia. The method used is descriptive research with case studies on two taxi companies, namely PT. Blue Bird Tbk (BIRD) and PT. Express Transindo Utama Tbk (TAXI) during the period 2014-2022. The variables studied were operating income, operating profit/loss, stock prices, and bankruptcy predictions using the Springate model. The results show that the emergence of online-based transportation affects decreasing operating income, operating profit, and stock prices in both companies. The potential for bankruptcy also increases with decrease in income and operating profit. Nevertheless, BIRD can endure in the era of disruption by innovating in services and collaborating with online transportation companies. On the other hand, TAXI’s efforts to innovate have not yielded results, leading to a lack of significant improvement signals in the company’s performance. Adaptability, innovation strategies, and collaboration are identified as key factors for the success of conventional taxi companies in surviving the era of disruption. Keywords: disruption era, online transportation, conventional taxis, bankruptcy